Varying aggregate sizes, plasticizers, and supplementary cementitious materials to efficiently use Portland clinker in concrete - Asahi Amitani; Sabbie A Miller (Environmental Research: Infrastructure and Sustainability)
Mitigating greenhouse gas (GHG) emissions from the production of concrete, a critical infrastructure material around the world, has been highlighted as necessary to meet climate change goals. Concrete is made of water, aggregates (e.g. crushed rocks), and Portland cement (PC), a hydraulic binder. PC is the primary source of GHG emissions from concrete, a function of the emissions derived from the production of its clinker, a kilned, quenched material composed of calcium silicates that, by mass, makes up the majority of PC. While considerable attention has been given to reducing the GHG emissions from PC manufacture, better utilization of other resources used in concrete can lower the demand for the level of clinker necessary in any given mixture. In this work, we examine how changing the size of aggregates, the use of a superplasticizer (SP), and the use of supplementary cementitious materials (SCMs) can lower GHG emissions from concrete. We derive a system of equations based fundamentally on standard mixture proportioning guidelines to determine the most efficient use of PC in a concrete mixture for specified strength and workability, and we quantify GHG emissions using life cycle assessment methods. Findings show that the use of reactive SCMs can contribute to reduced GHG emissions, as can the use of a higher maximum aggregate diameter and higher SP dosage. Our models also suggest that a concrete producer could follow standard mixture proportioning guidelines and yield a mixture that has over 2 times the PC content needed. The efficient use of PC within concrete mixtures by appropriately selecting other constituents can lower GHG emissions, contributing to climate change goals.